Individual differences in effective interview design: Factors affecting question choice. (20th July 2020) - Speer, Andrew B.; Tenbrink, Andrew P.; Schwendeman, Michael G.; Wegmeyer, Lauren J.
Abstract: Despite the evidence that structured interviews are superior to unstructured interviews, interviewers remain reluctant to use them for personnel selection. The current research replicated and extended recent research examining how individual differences relate to the ability to identify effective interview questions. Question judgments were made across questions that varied substantially in quality and across two different jobs. Across two samples of data, respondents evaluated past behavioral and traditional interview questions more favorably than oddball questions and questions about job‐irrelevant competencies. Furthermore, general mental ability and social aptitude were strongly related to skill in identifying effective interview questions, with results suggesting these traits are associated with customizing questions to specific job contexts.